Roy Campbell - Wright, David (Writers and Their Work Series., 1961)
Roy Campbell was born in 1901 in Natal, and died in Portugal, after a life of great variety and achievement. In this essay Mr. Wright assesses Campbell's work in poetry and prose. He justly says that 'he affirmed, in his life and in his work, the validity of the poetic vocation, its serious character and its morality of delight, in an age when its existence is either denied or, by pedants and cultural organisation, polluted by various subtle and well-meant fo.